Liquid metal engineering and technology. Volume 1 proceedings of the third international conference held in Oxford on 9-13 April 1984. (British Nuclear Energy Society, 1984)
Papers are grouped by session: 'Steam Generators: Sodium/Water Leak Behaviour', 'On-line Impurity Monitoring', 'Tribology and Static Adhesion', 'Steam Generators: Sodium/Water Leak Detection', 'Thermal Hydraulics and Heat Transfer' and more.